PERBANDINGAN ANTARA HUKUM POSITIF DENGAN HUKUM ISLAM MENGENAI PEMBAGIAN HARTA BERSAMA AKIBAT PERCERAIAN - Masrokimin Masrokimin (Jurnal Ius Constituendum, 2016)
Positive Law of the treasure together for this is still not the Resolute to provide rules on the division of the problem treasure together all still feel ambiguous are no rules that specify the split of the treasure together in KHI (Compilation of Islamic Law) by dividing equally that half to his wife and half for husband , but in a specific case by case if all decisions jointly owned by such disputes will be found, less able to reflect the sense of justice by a particular party, the Islamic law there is no clear division of the treasure together, both in classical and contemporary jurisprudence, is not even found in Al-Quran or Al-Hadith on this issue, there are certain differences in solving problems of common property, from differences in both the Positive Law and Islamic Law regarding subdivision and settlement when there is a dispute about the treasure joint will be obtainedcomparison, the ratio will be understood as a positive step in understanding and explore how the distribution and completion of this common treasure, so that would be obtained justice for those who want to resolving the problem treasure together.Legal dispute settlement joint property according to the Law-Marriage Law No. 1 of 1974 and the Compilation of Islamic Law that according to article 37, that is: "If the marriage broke up because of divorce, the joint property set by statute each-each, any property obtained during marriage is community property, where as in the compilation of Islamic Law, joint property due to divorce will be split half and half for the husband to the wife. The judge in the consideration of the joint property dispute resolution processes as a result of the divorce, the judge must be able to contribute to find a law that make of public order and sense of justice among the parties in addition to the meaning of legal certainty and legal protection. The procedure for resolving disputes together limitative property has been set in the civil procedural law, ranging from the laws it until judge so submission concerning joint property dispute after their divorce. In the process of dispute resolution does not rule out treasure along with the reconciliation process or mediation outside the Judiciary or in Non-Litigation with principles-principles and basic-basic fairness amongpihak. In Islamic law principles for dispute resolution highly promoted because it will be much can find a sense of justice among between with attention to customary law and without prejudice to the other party. But when disputes the joint property is entered in the Litigation in court Judge precisely given the right to according in this settlement by way istimbath law as rights - the right of a judge that they have in accordance with the main points of the power of Justice.